2022
DOI: 10.1002/hyp.14517
|View full text |Cite
|
Sign up to set email alerts
|

Comparing headwater stream thermal sensitivity across two distinct regions in Northern California

Abstract: Thermal regimes in headwater streams are critical for freshwater ecological condition and habitat resilience to disturbance, and to inform sustainable forest management. However, stream temperatures vary depending on characteristics of the stream, catchment, or region. To improve our knowledge of stream thermal regimes, we collected stream and air temperature data along eight headwater streams in two regions in Northern California. Five streams were in the Coast Range, which is characterized by permeable sands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 105 publications
2
3
0
Order By: Relevance
“…This relationship is further supported by H‐2 having the lowest maximum water temperature and the lowest conductivity. Similar to our study, Wissler et al (2022) found that in the Cascade Range (North of the Sierra Nevada) thermal regimes were heavily influenced by groundwater and potentially snowmelt. Wissler et al (2022) also found that the rain‐dominated Coast Range had warmer water temperatures despite cooler air temperatures and more riparian cover, possibly because of reduced groundwater influence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This relationship is further supported by H‐2 having the lowest maximum water temperature and the lowest conductivity. Similar to our study, Wissler et al (2022) found that in the Cascade Range (North of the Sierra Nevada) thermal regimes were heavily influenced by groundwater and potentially snowmelt. Wissler et al (2022) also found that the rain‐dominated Coast Range had warmer water temperatures despite cooler air temperatures and more riparian cover, possibly because of reduced groundwater influence.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, Wissler et al (2022) found that in the Cascade Range (North of the Sierra Nevada) thermal regimes were heavily influenced by groundwater and potentially snowmelt. Wissler et al (2022) also found that the rain‐dominated Coast Range had warmer water temperatures despite cooler air temperatures and more riparian cover, possibly because of reduced groundwater influence. The observed negative relationship between discharge and maximum temperature supports the notion that reduced thermal buffering in smaller streams could leave some headwaters especially vulnerable to climate‐change induced low flows.…”
Section: Discussionsupporting
confidence: 91%
“…It thus remains to be seen whether such patterns would hold at broad scales, which would require a comparison of a substantially larger number of sites than the six investigated here. While other studies have investigated how site characteristics, such as shading, stream width, and drainage area, are related to temperature changes (Nelson & Palmer, 2007; Somers et al, 2013; Wissler et al, 2022; Zahn et al, 2021), our study uniquely links these behaviours to event characteristics and identified hydrograph metrics (e.g., Qpeak/VQ, ΔQ) as important predictors for the temperature patterns (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the thermal sensitivity for each site from the linear regression slope of the daily mean air‐water temperature relationship (Kelleher et al, 2012; Snyder et al, 2015; Wissler et al, 2022). Air temperature data were collected from a geographically centralised weather station (Eastern West Virginia Regional Airport, GHCND:USW00013734) and adjusted to expected air temperatures for each site based on a lapse rate of 9.8°C per km of elevation change (Stull, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the thermal sensitivity for each site from the linear regression slope of the daily mean air-water temperature relationship (Kelleher et al, 2012;Snyder et al, 2015;Wissler et al, 2022).…”
Section: Environmental Covariatesmentioning
confidence: 99%